CRITERIA, INDICATORS AND LEVELS OF FORMATION PROFESSIONAL COMPETENCE OF A FUTURE TEACHER PHILOLOGICAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the criteria, characteristics, and levels of formation of the professional competence of future teachers of philological subjects.
Keywords: professional competence of future teacher of philological subjects; the criteria; characteristics and levels of formation